Cell Encapsulation Within Alginate Microcapsules: Immunological Challenges and Outlook - Ashimova, Assem; Yegorov, Sergey; Negmetzhanov, Baurzhan; Hortelano, Gonzalo (Frontiers in Bioengineering and Biotechnology, 2019)
Cell encapsulation is a bioengineering technology that provides live allogeneic or xenogeneic cells packaged in a semipermeable immune-isolating membrane for therapeutic applications. The concept of cell encapsulation was first proposed almost nine decades ago, however, and despite its potential, the technology has yet to deliver its promise. The few clinical trials based on cell encapsulation have not led to any licensed therapies. Progress in the field has been slow, in part due to the complexity of the technology, but also because of the difficulties encountered when trying to prevent the immune responses generated by the various microcapsule components, namely the polymer, the encapsulated cells, the therapeutic transgenes and the DNA vectors used to genetically engineer encapsulated cells. While the immune responses induced by polymers such as alginate can be minimized using highly purified materials, the need to cope with the immunogenicity of encapsulated cells is increasingly seen as key in preventing the immune rejection of microcapsules. The encapsulated cells are recognized by the host immune cells through a bidirectional exchange of immune mediators, which induce both the adaptive and innate immune responses against the engrafted capsules. The potential strategies to cope with the immunogenicity of encapsulated cells include the selective diffusion restriction of immune mediators through capsule pores and more recently inclusion in microcapsules of immune modulators such as CXCL12. Combining these strategies with the use of well-characterized cell lines harboring the immunomodulatory properties of stem cells should encourage the incorporation of cell encapsulation technology in state-of-the-art drug development.